Islamic Counseling Perspective on Stigma and Inequality in Health Service Access Among Scavengers in Makassar City - A Nurul Mutmainnah; Muhammad Syukur; Firdaus W Suhaeb (Institut Agama Islam Negeri Parepare, 2026)
Informal waste pickers are key actors in the urban recycling system; however, their access to healthcare remains unequal. This study explores the gap in access to and experiences of healthcare services between waste pickers and waste business owners/managers in Makassar, Indonesia. A comparative qualitative approach was used through in-depth interviews with 15 waste pickers, 10 business owners/managers, and 5 health workers, complemented by observations at the Antang temporary waste disposal site (TPS) and three nearby community health centers (Puskesmas). The findings indicate that inequalities are shaped by the interaction of economic, symbolic, and institutional factors. Waste pickers face unstable daily incomes, indirect costs of seeking treatment, limited administrative and digital literacy, longer waiting times, and the stigma associated with